Effect of shear span-to-depth ratio on the mechanical behavior of composite sandwich beams with GFRP ribs and balsa wood core materials. (September 2020) - Zhang, Fubin; Xu, Jing; Esther, Bwiza; Lu, Haijun; Fang, Hai; Liu, Weiqing
Abstract: This study investigated the effect of shear span-to-depth ( a / d ) ratio on the mechanical behavior of composite sandwich beams, composed of glass fiber reinforced polymer (GFRP) skins, balsa wood core, and GFRP ribs. Three-point bending tests were carried out on fifteen specimens to verify the effects of the a / d ratio, varying from 1 to 6, and GFRP ribs on the deflections, failure load, and failure modes of sandwich beams. Test results indicated that the a / d ratio plays a major role in beam deflections, which decreased 74–1418% as the a / d ratio varying from 1 to 6. All beams exhibited deflections at failure of span/124 to span/35. Specimens failed in balsa wood core shear failure while a / d  ≤ 4, whereas it failed in top skin compression failure when a / d ratio equal to 6. Increasing the GFRP ribs thickness from zero to 2.4 mm, the failure load of sandwich beams increased by 23–75%. Moreover, the ultimate moment increased by 70–323% as the a / d ratio increases from 1 to 6. In addition, for specimens with a / d equal to 4, the failure load and stiffness of sandwich structures with balsa wood core was 79–209% and 90–246% higher than those of specimens with different densities of light-weight foam core. A simplified analytical model accounting for the influence of GFRP ribs on stiffness and strength of the sandwich beam was developed and validated against experimental results. Analysis shows that flexure became more dominant as the a / d ratio increases. The shear deformation contribution of the balsa wood core is over 50% in beams with a / d  ≤ 3, while the value is only 20% for beams with a / d equal to 6. The proposed analytical model which accounts for the combined effect of the GFRP ribs agrees well with the experimental results. Highlights: Investigated the effect of shear span-to-depth ( a / d ) ratio on the mechanical behavior of composite sandwich beams. The  a / d  ratio plays a major role in beam deflections, which decreased 74–1418% as the  a / d  ratio varying from 1 to 6. All beams exhibited deflections at failure of span/124 to span/35. The failure load and stiffness of sandwich structures with balsa wood core was increased by 79–209% and 90–246% respectively..